The Application of the Constitutional Convention in Malaysia - Nazri Muslim; Osman Md Rasip; Khairul Hamimah Mohammad Jodi; Abdullah Ibrahim; Otong Rosadi (Canadian Center of Science and Education, 2020)
In Malaysia, there is no one institution that can outdo the supremacy of the Federal Constitution. Even the three government bodies that refer to the power separation doctrine which is the legislative, judiciary and executive bodies even the Yang di-Pertuan Agong are under this Federal Constitution. The constitution can be divided into two, written and non-written constitution. The written constitution is the form of constitution that is gathered and arranged in one document. The non-written counterpart encompasses all of the constitutional principles not compiled in one document such as the law endorsed by the Parliament and the verdicts of the court such as in the United Kingdom. Other than the constitution, there are certain practices that are thought to be part of the principles of the constitution. This is known as the Constitutional Convention or the customary practice of the Constitution. Constitutional convention is a non-legislative practice and it is similar to the political ethics and not enforced in court. Although it seems trivial, it is important for this practice to be complied with, otherwise it is difficult for the constitution to work successfully as the constitutional convention cannot be brought to court and forced to be obeyed. Thus, the discussion of this article rests on the constitutional convention in terms of the social contract, the appointment of the Prime Minister, the appointment of the country’s main positions and collective responsibility. (Abstract by authors)